Should research and publication be included in the undergraduate medical curriculum? - Pradhan, Nabees Man Singh (Journal of Patan Academy of Health Sciences, 2022)
Scientific papers are the key to advancements that humans have leaped through in different fields of science. Members of the scientific community use research to explore, discover and accumulate knowledge/skills to contribute to society which makes humans stand out among all the existing species on the planet. The publication has been used as a tool to document the findings/discoveries, and also to build up the foundation of the knowledge which has kept growing over time for humans to have the ability to develop complex and advanced stuff, which in other words is termed ‘development.’